2021
DOI: 10.3390/polym13183038
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Polyvinylpyrrolidone K90 and Poloxamer 407 Self-Assembled Nanomicelles: Enhanced Topical Ocular Delivery of Artemisinin

Abstract: Age-related macular degeneration is a multifactorial disease affecting the posterior segment of the eye and is characterized by aberrant nascent blood vessels that leak blood and fluid. It ends with vision loss. In the present study, artemisinin which is poorly water-soluble and has potent anti-angiogenic and anti-inflammatory properties was formulated into nanomicelles and characterized for its ocular application and anti-angiogenic activity using a CAM assay. Artemisinin-loaded nanomicelles were prepared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…P407 might increase corneal permeation by further increasing the water-solubility of DXM. Additionally, it can remove the phospholipids from the epithelial cell membrane by complexation but does not damage the membrane; furthermore, P407 can relax the cell junctions of the epithelium resulting in the increased influx of DXM through the cornea [ 61 ]. In our work, P407 enhanced drug penetration.…”
Section: Discussionmentioning
confidence: 99%
“…P407 might increase corneal permeation by further increasing the water-solubility of DXM. Additionally, it can remove the phospholipids from the epithelial cell membrane by complexation but does not damage the membrane; furthermore, P407 can relax the cell junctions of the epithelium resulting in the increased influx of DXM through the cornea [ 61 ]. In our work, P407 enhanced drug penetration.…”
Section: Discussionmentioning
confidence: 99%
“…1)Artemisinin alone has poor water solubility, and it needs to effectively treat AMD by improving water solubility and corneal permeability. There is a need to develop nanoparticle systems to facilitate studies related to ocular bioavailability and e cacy of incorporated drugs and to develop rational protocols [12]. 2)At present, experiments have con rmed the antioxidant, anti-in ammatory and anti-neovascular effects of artemisinin and its derivatives, but because of its bidirectional regulation, more experiments are needed to study its dosage in the treatment of AMD at different stages, which should consider how to solve the side effects caused by different doses, so that artemisinin and its derivatives can be better used for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Direct or indirect inhibition of abnormal expression of VEGF may provide an effective treatment plan for CNV treatment. Interestingly, studies have found that artemisinin and its derivatives can directly or indirectly inhibit angiogenesis [12,80], the underlying mechanism is shown in Fig. 3.…”
Section: Choroidal Neovascularizationmentioning
confidence: 99%
“…Nanomicelles are the commonly used carrier to deliver the drug to the clear aqueous solution. It is made of surfactants or polymers that are amphiphilic in nature, and have the property to self-assemble themselves in the micelle form [54]. Micelles are of three types: regular, reverse, and unimolecular.…”
Section: Nanomicellesmentioning
confidence: 99%